Success stories and continuing challenges: A longitudinal analysis of gender-ethnic wage gaps in the UK - Simonetta Longhi (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2025)
This paper investigates the evolution of ethnic wage gaps among men and women in the UK over the period 1993-2023. The results show reductions in wage gaps among all South Asian groups, which are driven by higher educational attainment and occupational advancement. In contrast, wage gaps persist for Black ethnic groups. While for Black Caribbeans a key issue is lower levels education, for Black Africans the high proportion of foreign-born individuals limits their returns on education. These trends suggest a reordering of the wage gap hierarchy over time, with Black groups expected to experience the largest disparities in the future, instead of the historically disadvantaged Pakistani and Bangladeshi groups.
Keywords: J31; J71; 330; ethnic wage gaps; gender wage gaps; wage gap trends; impact of characteristics; labour force participation